(Nu HRAM)QÆ HRIZANTEM hRIZONTOWI^A(B. (NsERÆQ LISTÆWOK DO (B70-(NRÆ^^Q TWOR^OÇ DÆQLXNOSTÆ UKRAÇNSXKOGO PISXMENNIKA wASILQ mÆSEWI^A (B/s)E - (NwASKAN(B, (Nw(B. (Nw(B.s ((NwASILX wASILXOWI^(B)s; (NdEM^ENKO(B, (Nw(B. (Ng(B.s ((Nw)QÆTALÆJ gRIGOROWI^(B)s)E; (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s; (NdOWBU[(B, (No(B. )Qæ.s)E ((NoLEKSANDR )QæWANOWI^(B)s)E; (NkITAJGORODSXKA(B, (Nw(B. (Nm(B.s ((Nw)QÆRA mIKITÆWNA(B)s)E; (Nt)QÆTOW(B, (Nw(B. (Nt(B.s)E ((NwASILX tIHONOWI^(B)s; (Nm)QÆSEWI^(B, (Nw(B. (Nh(B.s)E ((NwASILX hR)QÆZONTOWI^(B)s)E; (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s ((N~ERN)QÆWCÆ (B:s)E (NrODOW)QÆD(B,s)E, 2022)
(NsER)QÆQ LISTÆWOK (B"(Nu HRAMÆ HRIZANTEM hRIZONTOWI^A(B. (NdO (B70-(NRÆ^^Q TWOR^OÇ DÆQLXNOSTÆ UKRAÇNSXKOGO PISXMENNIKA wASILQ mÆSEWI^A(B" (NPRISWQ^ENA UKRAÇNSXKOMU POETU Z bUKOWINI(B, (NLAUREATU BAGATXOH LÆTERATURNIH PREMÆJ(B, (N^LENU nACÆONALXNIH SPÆLOK VURNALÆSTÆW TA PISXMENNIKÆW uKRAÇNI(B. (NpOETI w(B. (NkITAJGORODSXKA(B, (No(B. (NdOWBU[(B, (Nw(B. (NdEM^ENKO(B, (Nw(B. (NmÆSEWI^ TA ÆN[Æ (B(7 (NAWTORÆW(B) (NPRISWQ^U@TX SWOÇ WÆR[Æ POETU(B-(NBUKOWINC@(B.s)E
(NpRO)QÃKT ~ERNÆWECXKOÇ OBLASNOÇ ORGANÆZACÆÇ nACÆONALXNOÇ SPÆLKI PISXMENNIKÆW uKRAÇNIs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKAs)E -- (NpOEZ)QÆQ(B.s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E